DSP Analysis of the Impact of Product Quality and Lifestyle on Gen-Z Impulse Buying Decisions on E-Commerce Products (Case Study of College Students in Surakarta City) - Sri Prihatin, Diyah Ayu; Heni Susilowati (Universitas Pamulang, 2024)
The purpose of this study is to analyze the influence of product quality and lifestyle on impulse buying decisions for Shopee e-commerce. This study uses a quantitative research type. The population in this study were Gen Z students in the city of Surakarta. The sampling technique used a non-random sampling technique with a purposive sampling method and obtained a total of 100 respondents. The data collection technique used a questionnaire with Likert scale parameters. The data analysis technique used multiple linear regression assisted by SPSS version 29 software for data processing. The results showed that product quality and lifestyle variables had a significant influence on impulse buying decisions for Shopee e-commerce products, where the significance value was below 0.05. The results of the F test obtained an F-count value of 28.690 which was greater than the F-table value of 3.089. From the results of the determination coefficient test, 35.9% of the purchasing decision variables were influenced by product quality and lifestyle variables, while the remaining 64.1% were explained by the influence of other factors or variables outside the model such as product quality, lifestyle and others that were not discussed in this study.